2019
DOI: 10.1080/02670844.2018.1463679
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of heat-treated duplex electroless nickel coatings

Abstract: Electroless nickel coatings present complementary properties: coatings formed using hypophosphite present usually better corrosion resistance while those made with borohydride present better mechanical and wear properties. Duplex coatings, combining both kinds of deposits, are designed to combine features of both nickel-phosphorus (ENP) and nickel-boron (ENB) coatings. In this study, monolayer and bilayer coatings were synthesised on mild steel substrates, in various combinations of ENP and ENB, with a total t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…From a morphological point of view, NiB-Bi coatings present morphologic variations in the film between the outer part and the inner part. NiB-Pb presents a completely columnar structure [22,36,37]. As explained before, this difference is caused by the high redox potential of Bi +3 compared with Pb 2+ .…”
Section: Comparison Of Electroless Nib-bi and Nib-pbmentioning
confidence: 84%
“…From a morphological point of view, NiB-Bi coatings present morphologic variations in the film between the outer part and the inner part. NiB-Pb presents a completely columnar structure [22,36,37]. As explained before, this difference is caused by the high redox potential of Bi +3 compared with Pb 2+ .…”
Section: Comparison Of Electroless Nib-bi and Nib-pbmentioning
confidence: 84%
“…The chemistry of coatings is not only influenced by the reducing agent and operating conditions but also by the type of stabilizer. DMABreduced coating usually contains less boron than those from borohydride-based baths, which can contain up to 8 wt% boron [145]. Experiments carried out on NaBH 4 -reduced baths have shown that the percentage of boron increases with the amount of reducing agent in the bath and with temperature [145,146].…”
Section: Composition and Morphology Of En-b Coatings And The Influenc...mentioning
confidence: 99%
“…DMABreduced coating usually contains less boron than those from borohydride-based baths, which can contain up to 8 wt% boron [145]. Experiments carried out on NaBH 4 -reduced baths have shown that the percentage of boron increases with the amount of reducing agent in the bath and with temperature [145,146]. The most frequent chemistry of EN-B deposits is 5 to 6 wt% B with or without incorporated stabilizing agent [17].…”
Section: Composition and Morphology Of En-b Coatings And The Influenc...mentioning
confidence: 99%
“…The ED process of Ni coatings has been studied in depth lately due to their mechanical properties or resistance to corrosion, wear and friction [24][25][26] and their electrocatalytic activity [27]. Overall, ED of Ni could lead to Ni-X-P or Ni-X-B coatings, where X could be an alloying metal or a composite particle (such as W, Cu, Zn, Co, CNTs), P is phosphorus and B is boron [14,25].…”
Section: Introductionmentioning
confidence: 99%